Exploration and Practice of Blended Teaching for Courses in the Context of Digital Transformation - Wang Lingzhi; Ma Haiyang; Liu Yang (SHS Web of Conferences, 2024)
The curriculum is the basic basis and carrier of educational and teaching activities, and it is the core of the digital transformation of education. With the continuous deep integration of digital technology in the curriculum and teaching, how to effectively deal with the impact and influence of the continuous innovation and breakthrough of digital technology on the curriculum and teaching, and better promote students’ inquiry and personalized learning has become an urgent problem in front of us. This paper focuses on the digital transformation of the background of the curriculum teaching issues, aviation maintenance management course as an example to carry out analysis and research, which can promote the deep integration of digital technology and curriculum teaching to provide reference and reference..